Changes in the Serum Fatty Acid Profile After Anhepatic Phase of Orthotopic Liver Transplantation Procedure - Hliwa, Aleksandra; Mika, Adriana; Sledzinski, Maciej; Laski, Dariusz; Ramos-Molina, Bruno; Sledzinski, Tomasz (Frontiers in Physiology, 2022)
During the orthotopic liver transplantation (OLT) the patients’ body remains deprived of this organ for some time, which could cause critical changes in the levels of various metabolites in the circulation, including fatty acids (FAs). Thus, the aim of this study was to determine whether the liver transplantation procedure leads to significant changes in FAs profile in serum lipids after anhepatic phase. Our gas chromatography – mass spectrometry analysis revealed that after transplantation serum levels of myristic and palmitic acids were significantly decreased, whereas serum levels of very long chain FAs containing 20 or more carbons in their chains were increased. These results indicate that ahnepatic phase during liver transplantation produce significant changes in serum FA levels, and emphasizes the role of the liver in metabolism of very long chain fatty acids.